1997
DOI: 10.1046/j.1365-2249.1997.d01-1004.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the rate of donor leucocyte migration between natural and drug-assisted tolerance following rat liver transplantation

Abstract: SUMMARYThe number involved in and the rate of migration of donor leucocytes into the following recipient organs (spleen, thymus, bone marrow, lung and mesenteric lymph nodes) were measured in two rat models of orthotopic liver transplantation (OLT) using donor-specific MHC class I antibodies. The first OLT model is one that does not require immunosuppression in order to achieve tolerance and involved the transplantation of DA (MHC haplotype, RT1 a ) livers into PVG (RT1 c ) recipients. The second model was one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…D A livers were orthotopically transplanted into D A (n = 18), PVG (n = 18), and LEW (n = 18) recipients. As reported previously [11], OLT (DA-PVG) rats naturally overcome rejection while all OLT (DA-LEW) rats die from acute rejection within 14 days. Syngeneic OLT (DA-DA) rats were used as controls since no rejection occurs and rejection-related factors are eliminated.…”
Section: Olt and Liver Samplessupporting
confidence: 71%
“…D A livers were orthotopically transplanted into D A (n = 18), PVG (n = 18), and LEW (n = 18) recipients. As reported previously [11], OLT (DA-PVG) rats naturally overcome rejection while all OLT (DA-LEW) rats die from acute rejection within 14 days. Syngeneic OLT (DA-DA) rats were used as controls since no rejection occurs and rejection-related factors are eliminated.…”
Section: Olt and Liver Samplessupporting
confidence: 71%
“…Further experiments from the same group of investigators, and in the same transplant combinations, subsequently demonstrated that higher levels of IL-2 and IFN-mRNA were found in celiac lymph nodes and spleen in the spontaneously tolerant combination of (LEW-DA) when compared with the converse rejector combination (DA-LEW). 1,15 When considering the phenomenon of microchimerism on the transplant process 1,[4][5][6]15,23 it is difficult to understand why higher levels of IL-2 and IFN-would be found only in lymphoid organs and not similarly increasing in the transplanted liver. The observed paradoxical immune activation in the lymphoid tissues of tolerant animals has been suggested to be associated with a high-dose tolerance mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive therapy using drugs such as cyclosporin A (CsA) or FK506 are not required for orthotopic liver transplantation (OLT) between the inbred rat strains DA (MHC haplotype RT1 a ) and PVG (RT1 c ) to achieve allograft tolerance. [1][2][3][4][5][6] Animals transplanted in this combination, despite a complete major histocompatibility complex (MHC) mismatch, do not reject the transplanted allograft and many mechanisms have been proposed to account for this phenomenon. These have included the presence of unusual soluble MHC class I molecules synthesised by the liver, [7][8][9] presence of anti-MHC class I antibodies, 4,10-12 a higher rate of donor cell migration, 5,6 expression of novel immunosuppressive proteins 13, 14 and possible high-dose-activation-associated tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37 DA livers were orthotopically transplanted into DA, PVG or LEW recipients. As reported previously, 38 OLT (DA-PVG) rats naturally overcome rejection without using any type of immunosuppressants (spontaneous tolerance model). In contrast, all OLT (DA-LEW) rats die from acute rejection within 14 days (acute rejection model).…”
Section: Rat Olt and Liver Samples Collectionmentioning
confidence: 83%